Exploring health literacy in nursing students of Chongqing, China: a cross-sectional survey using the health literacy questionnaire. (October 2016) - Zhang, Yan; Zhang, Fan; Hu, Ping; Huang, Wenjie; Lu, Lu; Bai, Ruixue; Zhao, Yong
Abstract: Background: Health literacy is important in public health and health care, particularly in effective communication between patients and nurses. The aim of this study was to explore the health literacy level and its influence factors in undergraduate nursing students. Methods: We did a cross-sectional study by stratified sampling of nurses studying at the medical university in Chongqing, south-western China. Nurses had to attend class, be willing to participate, and be younger than 28 years. We used the health literacy questionnaire (HLQ), which was created by Osborne and colleagues, to assess literacy. Analyses were done with χ 2 tests, ANOVA, and multiple linear regression models. We set the low health literacy to scores lower than 60% of the total score and the high health literacy to scores higher than 80% of the total score. The study protocol was approved by the Ethics Committee of Chongqing Medical University (record number 2015002). And we obtained written informed consent from all participants. The study protocol was approved by the Ethics Committee of Chongqing Medical University (record number 2015002). Findings: Between March 23, 2015, and April 16, 2015, a total of 612 undergraduate nursing students filled the survey, 316 were in grade one, 168 in grade two, and 128 in grade three. The total score of HLQ was 40·00; the mean score of HLQ was 26·18 (SD 3·95). The mean scores of HLQ in nine scales, including (1) feeling understood and supported by healthcare providers, (2) having sufficient information to manage my health, (3) actively managing my health; (4) social support for health, (5) Appraisal of health information, (6) ability to actively engage with health-care providers, (7) navigating the health-care system, (8) ability to find good health information, and (9) understand health information well enough to know what to do were 2·16 (SD 0·57), 2·54 (0·47), 2·60 (0·49), 2·88 (0·46), 2·61 (0·46), 3·24 (0·76), 3·16 (0·69), 3·42 (0·65) and 3·56 (0·61), respectively. Participants with higher grades were more likely to have higher scores than those with lower grades in scales 1 to 9 (F=30·852, p<0·001; F=49·456, p<0·001; F=32·347, p<0·001; F=40·272, p<0·001; F=52·483, p<0·001; F=30·852, p<0·001; F=240·018, p<0·001; F=215·972, p<0·001; F=158·258, p<0·001 and F=200·215, p<0·001). Participants with average or higher socioeconomic status were more likely to have higher scores than those with lower socioeconomic status in scales 3, 6 to 9 (t=–2·127, p=0·034; t=–3·540, p<0·001; t=–3·756, p<0·001; t=–4·210, p<0·001 and t=–4·785, p<0·001).. Participants whose parent had completed high school had higher scores than those whose parents had not completed high school in scales 5 to 9 (t=–2·044, p=0·041; t=–3·866, p<0·001; t=–3·886, p<0·001; t=–3·268, p=0·001 and t=–6·255, p<0·001). Regression analysis showed that higher grades (t=9·418, p<0·001 and t=16·923, p<0·001), higher parent's level of education (t=5·366, p<0·001), and higher socioeconomic status (t=4·764, p<0·001) were associated with higher scores of the HLQ. Interpretation: Our findings indicate that the health literacy levels of the undergraduate nursing students are insufficient. We suggest that school should pay more attention to cultivate nursing students' health literacy level. Funding: This project was supported by theHumanity and Social Science Foundation of China's Ministry of Education (15YJA860020 ).